Within Indian wars and the Wounded Knee massacre - Syukrianto, Ristan Taufiq (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
Besides recorded in textbooks, historical events sometimes are adopted into literary works. Rebecca Wiles’ Bury Me at Wounded Knee is one of which since it portrays the Indian Wars and the Wounded Knee Massacre on 29 December 1890. The clause Bury Me at Wounded Knee in the poem is a form of self-determination of Native Americans. This paper aims at mapping the causal relation of historical events found in the poem to examine the Native Americans’’ self-determination inside it. As the basis, the paper employs the Historicism theory and Self-Determination theory (SDT) about autonomous and controlled motivations. The results found that the Native Americans’ self-determination in the poem is an undermined one. It is built by their internal autonomous motivation of deeply rooted culture and beliefs. However, the encroachments of the U.S. government who seized their rights, acted as controlled extrinsic motivations, internalized and thwarted the intrinsic motivation so that the self-determination is undermined. It decreases in the degree from an eagerness to act and resist to merely a wish of being buried in the location where they die and think of extinction.